2023
DOI: 10.1007/s00068-022-02205-5
|View full text |Cite
|
Sign up to set email alerts
|

Is hospital volume related to quality of hip fracture care? Analysis of 43,538 patients and 68 hospitals from the Dutch Hip Fracture Audit

Abstract: Purpose Evidence for a hospital volume–outcome relationship in hip fracture surgery is inconclusive. This study aimed to analyze the association between hospital volume as a continuous parameter and several processes and outcomes of hip fracture care. Methods Adult patients registered in the nationwide Dutch Hip Fracture Audit (DHFA) between 2018 and 2020 were included. The association between annual hospital volume and turnaround times (time on the emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…For instance, the results of a retrospective multifacility cohort study indicated that the survival rate of patients with ovarian cancer may increase depending on the hospital volume [30]. Admission to a high-volume hospital may be associated with lower mortality or a higher quality of medical care, although some data suggest that large hospitals do not necessarily provide better medical care to every patient in proportion to hospital size [31,32]. To draw a solid conclusion, the association between SAB management quality and hospital size should be further explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the results of a retrospective multifacility cohort study indicated that the survival rate of patients with ovarian cancer may increase depending on the hospital volume [30]. Admission to a high-volume hospital may be associated with lower mortality or a higher quality of medical care, although some data suggest that large hospitals do not necessarily provide better medical care to every patient in proportion to hospital size [31,32]. To draw a solid conclusion, the association between SAB management quality and hospital size should be further explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the results of a retrospective multifacility cohort study indicated that the survival rate of patients with ovarian cancer may increase depending on hospital volume [31]. Admission to a high-volume hospital may be associated with lower mortality or higher quality of medical care, although some data suggest that large hospitals do not necessarily provide better medical care to every patient in proportion to hospital size [32,33]. The diagnostic accuracy and treatment strategies at small-scale hospitals may be suboptimal mainly due to the unavailability of in-hospital facilities for blood culture and a lack of current medical knowledge.…”
Section: Discussionmentioning
confidence: 99%